Obtaining and characterizing jambolan peel pulp powder through foam mat drying (Research, Society and Development, 2024)
Jambolão is a fruit that has been little explored in the food industry because it is very perishable, and this bioactive-rich food is wasted. The objective of the present study was to develop jambolão peel pulp powder using the foam bed drying method, aiming for its full use and nutritional and functional potential. This study developed a powder from the pulp and peel of jambolão by drying it in a foam mat. The fresh fruit was chemically characterized, and its phytochemical content and antioxidant activity were determined. The rind powder with jambolão pulp was developed with 25% maltodextrin, 5% pectin, and 3% emustab, and the same analyses were carried out. The powder's particle size and solubility were also analyzed. Among the results obtained, the high content of reducing sugars (9.2 %), total soluble solids (14.17 °Brix), total anthocyanins (76.32 mg.100 g -1), and antioxidant activity (DPPH) (93.3 %), as well as the low lipid content (0.03 %) stood out in the pulp with peel in nature. As for the powder obtained, the analysis showed a high concentration of ash (0.73 %), phenolic compounds (165.11 mg. 100 g -1 GAE), total anthocyanins (260.61 mg.100 g -1) vitamin C (227.57 mg.100 g -1) and high antioxidant activity (95.50 %). The solubility was 92 % and the granulometry was characterized as fine. It is concluded that the powder obtained has nutritional and functional potential and can be incorporated as an ingredient or natural additive in foods.